Evaluasi Program Karawang Cerdas Oleh Dinas Pendidikan Pemuda Dan Olahraga Kabupaten Karawang - Berliana Dwinoorocta F; Eka Yulyana Yulyana; Lina Aryani Aryani (Jurnal Pemerintahan dan Politik, 2022)
ABSTRACT The Karawang Smart Program is a Government Program by providing assistance in the form of educational scholarships for the people of Karawang Regency based on Regent Regulation No. 66 of 2018. The purpose of this study to describe how the Karawang Smart Program Evaluation by the Karawang Regency Youth and Sports Education Office is seen from the assessment of input, assessment on the process, the assessment of the output, and the assessment of the impact. This study uses a descriptive research method with a qualitative approach. Collecting data in this research by means of literature study followed by interviews, observation, documentation and triangulation. Based on the results of the study showed that: 1). The input dimensions are in accordance with the Technical Instructions made by the Department of Education, Youth and Sports, Karawang Regency 2). The implementation process encountered problems, especially at the beginning of the fiscal year. Lack of supervision for three years from the Disdikpora on aid recipients 3). The results of this Smart Karawang Program increase the Human Development Index in Karawang Regency 4). The impact of the Karawang Cerdas program has made the public's interest in education high. So from the results of this study it is suggested that the Department of Education, Youth and Sports of Karawang Regency as the organizer prepares optimally and evaluates every year so that it is right on target in accordance with the Regulation of the Regent of Karawang.  Keywords : Evaluation, Program, Smart Karawang, Department of Education Youth and Sports. ABSTRAK Program Karawang Cerdas merupakan Program Pemerintah berupa beasiswa Pendidikan bagi masyarakat Kabupaten Karawang berdasarkan Peraturan Bupati Nomor 66 Tahun 2018. Bertujuan untuk mendeskripsikan bagaimana Evaluasi Program Karawang Cerdas oleh Dinas Pendidikan Pemuda dan Olahraga Kabupaten Karawang dilihat dari penilaian terhadap input, penilaian terhadap proses, penilaian terhadap output, dan penilaian terhadap impack. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kualitatif. Pengumpulan data dengan cara studi pustaka yang dilanjutkan dengan wawancara, observasi, dokumentasi dan triangulasi. Hasil dari penelitian menunjukkan bahwa 1). Dimensi input sudah sesuai dengan Petunjuk Teknis yang dibuat oleh Dinas Pendidikan Pemuda dan Olahraga Kabupaten Karawang 2). Proses pelaksanaan terjadi kendala terutama di awal tahun anggaran. 3). Hasil adanya Program Karawang Cerdas ini meningkatnya Indeks Pembangunan Manusia di Kabupaten Karawang 4). Dampak dari adanya program Karawang Cerdas membuat animo masyarakat menjadi tinggi terhadap pendidikan. Kurangnya pengawasan selama tiga tahun dari pihak Disdikpora terhadap penerima bantuan. Maka dari hasil penelitian tersebut disarankan agar Dinas Pendidikan Pemuda dan Olahraga Kabupaten Karawang selaku penyelenggara mempersiapkan dengan optimal serta melakukan evaluasi setiap tahun agar tepat sasaran sesuai dengan Peraturan Bupati Karawang. Kata Kunci : Evaluasi, Program, Karawang Cerdas, Dinas Pendidikan Pemuda dan Olahraga.